2019
DOI: 10.1186/s12884-019-2518-x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and social consequences of non-invasive prenatal testing (NIPT): a scoping review

Abstract: BackgroundGenomics-based noninvasive prenatal tests (NIPT) allow screening for chromosomal anomalies such as Down syndrome (trisomy 21). The technique uses cell-free fetal DNA (cffDNA) that circulates in the maternal blood and is detectable from 5 weeks of gestation onwards. Parents who choose to undergo this relatively new test (introduced in 2011) might be aware of its positive features (i.e. clinical safety and ease of use); however, they might be less aware of the required decisions and accompanying intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 28 publications
(101 reference statements)
2
27
0
1
Order By: Relevance
“…The STAI-6 has been shown to be highly correlated with the 20-item STAI, and all internal consistency reliabilities are greater than 0.90 [ 20 ]. The STAI-6 has been used both as a self-administered and online questionnaires [ 21 – 23 ]. The Chinese version of the STAI was used in this survey [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The STAI-6 has been shown to be highly correlated with the 20-item STAI, and all internal consistency reliabilities are greater than 0.90 [ 20 ]. The STAI-6 has been used both as a self-administered and online questionnaires [ 21 – 23 ]. The Chinese version of the STAI was used in this survey [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…• A German review paper examined in detail five studies with validated instruments which had assessed anxiety, psychological distress and/or regret over decisions among women (14), while two studies had interviewed women or held focus group discussions. It was found that the women's anxiety decreased when the test results showed a low risk of trisomy.…”
Section: Women's Personal Experiences Of Niptmentioning
confidence: 99%
“…In many countries around the world, there is very little support from the public purse for these children, so the cost is born by the family. Here I review 12 recent studies that directly or indirectly address attitudes of pregnant couples to NIPT (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)21), only two of which (8,14) are theoretical discussions.…”
Section: Introductionmentioning
confidence: 99%
“…3 Non-invasive prenatal testing, which has no procedure-related risk of miscarriage, is currently unavailable on the National Health Service (NHS) because of the high false positive rate of almost 8%. 4 Prenatal diagnosis may prove undesirable to couples who find the option of pregnancy termination unacceptable for religious or personal reasons. Thus, alternative options available to avoid giving birth to an affected child include a change of partner, use of donor gametes, adoption or opting to forgo having children altogether.…”
Section: Introductionmentioning
confidence: 99%